Multigene Families in Trypanosoma cruzi and Their Role in Infectivity - De Pablos, Luis Miguel (American Society for Microbiology, 2012)
The Trypanosoma cruzi genome contains the most widely expanded content (∼12,000 genes) of the trypanosomatids sequenced to date. This expansion is reflected in the high number of repetitive sequences and particularly in the large quantity of genes that make up its multigene families. Recently it was discovered that the contents of these families vary between phylogenetically unrelated strains. We review the basic characteristics of trans-sialidases and mucins as part of the mechanisms of immune evasion of T. cruzi and as ligands and factors involved in the cross talk between the host cell and the parasite. We also show recently published data describing two new multigene families, DGF-1 and MASP, that form an important part of the scenario representing the complex biology of T. cruzi.